Ultra wideband antennas : design, methodologies, and performance - Galvan-Tejada, Giselle M.; Peyrot-Solis, Marco Antonio; Jardón Aguilar, Hildeberto (CRC Press is an imprint of Taylor & Francis Group, 2016)
Ultra Wideband Antennas: Design, Methodologies, and Performance presents the current state of the art of ultra wideband (UWB) antennas, from theory specific for these radiators to guidelines for the design of omnidirectional and directional UWB antennas. Offering a comprehensive overview of the latest UWB antenna research and development, this book:Discusses the developed theory for UWB antennas in frequency and time domainsDelivers a brief exposition of numerical methods for electromagnetics oriented to antennasDescribes solid-planar equivalence, which allows flat structures to be implemented.